Integrated and intelligently controlled unit for suspension freeze concentration: design and experimental verification. Issue 1 (31st December 2021) - Peng, Kewen; Yang, Hongkai; Yin, Huibin; Qin, Frank G. F.
Abstract: Suspension freeze concentration (SFC) can avoid denaturation while concentrating thermal-sensitive aqueous solutions. However, the complex treatment process and high capital cost severely limit its application in large-scale production. In this paper, a compact and integrated unit is devised to overcome these shortcomings and improve the operability of SFC. The unit is in a vertical layout and supports multistage treatment to successively condense the solution. Several innovative designs are made for the key components, including the helical blades in the scraped surface heat exchanger and a dual-use column for recrystallization and washing. The former helps to establish the circulation of solution and impose forces to compress the ice column, while the latter enables seamless switch between different processes. As the whole process of SFC is well known to be time-consuming and labor-intensive, an intelligent controlling system is installed on the unit to realize on-site and/or remote monitoring and adjustment of the treatment. A concentration experiment using apple juice was conducted to verify the design and demonstrate the advantages. The results show that high-quality solutions were obtained with this unit. The recovery yields of the soluble solids and nutrients components are over 98.5% and 80.0%, respectively. Based on the work principles of the freezing and washing process in this design, the mechanism behind the superior recovery yields is analyzed. This study opens up a potential route for scaling up SFC and is expected to stimulate further work to achieve industrial application.